2011
DOI: 10.1063/1.3592350
|View full text |Cite
|
Sign up to set email alerts
|

Nanothermochromics with VO2-based core-shell structures: Calculated luminous and solar optical properties

Abstract: Composites including VO 2 -based thermochromic nanoparticles are able to combine high luminous transmittance T lum with a significant modulation of the solar energy transmittance DT sol at a "critical" temperature in the vicinity of room temperature. Thus nanothermochromics is of much interest for energy efficient fenestration and offers advantages over thermochromic VO 2 -based thin films. This paper presents calculations based on effective medium theory applied to dilute suspensions of core-shell nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 59 publications
0
75
0
2
Order By: Relevance
“…41 It was recently realized that nanothermochromism-involving VO 2 -based nanoparticles-can entail optical properties of primary interest for energy efficient fenestration. 11,[65][66][67] Consequently it is of great importance to develop efficient methods to prepare such nanoparticles in large quantities and over extended surfaces. In fact, there have been numerous prior studies on VO 2 -based nanoparticles, and recent investigations have been conducted with hydrothermal/solvothermal/colloidal techniques, 27,49,50,64, vapor transport, 56,[109][110][111][112][113][114][115] anodization, 116 polymer-assisted deposition, 117,118 and templating.…”
Section: Introductionmentioning
confidence: 99%
“…41 It was recently realized that nanothermochromism-involving VO 2 -based nanoparticles-can entail optical properties of primary interest for energy efficient fenestration. 11,[65][66][67] Consequently it is of great importance to develop efficient methods to prepare such nanoparticles in large quantities and over extended surfaces. In fact, there have been numerous prior studies on VO 2 -based nanoparticles, and recent investigations have been conducted with hydrothermal/solvothermal/colloidal techniques, 27,49,50,64, vapor transport, 56,[109][110][111][112][113][114][115] anodization, 116 polymer-assisted deposition, 117,118 and templating.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that some or all of these oxide layers are able to impart oxidation protection of the underlying VO 2 . We also note that VO 2 -based nanoparticles may be of considerable interest for TC fenestration [11,[16][17][18]. Core-shell structures have been investigated recently with VO 2 cores surrounded by shells comprised of SiO 2 [44][45][46][47][48] or TiO 2 [49][50][51] and, again, the top layer may serve as oxidation protection.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…TC fenestration has been discussed for several decades [2][3][4][5][6][7][8][9][10], but practical implementation has been hampered by performance deficiencies such as a too high value of τ c , too large luminous absorptance, and too small modulation of the solar energy throughput [11]. However, there has been substantial progress towards the alleviation of all of these obstacles, and it is well known that tungsten doping can decrease τ c to room temperature [11,12], that luminous absorptance can be lowered by magnesium doping [13][14][15][16], and that solar energy modulation can be boosted by invoking VO 2 -based nanoparticles rather than thin films [16][17][18]. Another obvious requirement for practical implementation of TC VO 2 -based films and nanoparticles is that they must maintain their desirable properties during extended periods of time, which is far from obvious since V 2 O 5 , not VO 2 , is the thermodynamically stable oxide [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] Furthermore, antireflection (AR) coatings are able to improve T lum and ΔT sol , and especially good properties have been reported for five-layer coatings of alternating TiO 2 and VO 2 . 2,3 Recent modeling studies on "nanothermochromics" 4,5 have shown that VO 2 nanoparticles can offer significantly higher values of T lum and ΔT sol than films, and these new possibilities have led to a burst of research on such nanoparticles. 6,9,19,22,25,[30][31][32][33][34] 25 This paper is outlined as follows: Section II reports on the samples and treats sputter deposition, compositional and structural data, and optical characterization and properties; this section also contains a discussion of sample quality which-as found in recent work of ours 9 -may be critically dependent on several aspects of the thin film preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The overarching goal is to assess VO 2 -based materials for energy efficient fenestration, and the present paper is a sequel to earlier ones. [1][2][3][4][5][6][7][8][9][10] Vanadium dioxide is a well known thermochromic material. 11 It undergoes a first-order metal-to-insulator transition, accompanied by a crystal structure transformation from monoclinic (M 1 ) to tetragonal rutile, at a critical temperature τ c ≈ 68 °C.…”
Section: Introductionmentioning
confidence: 99%